2020
DOI: 10.3390/joitmc6040138
|View full text |Cite
|
Sign up to set email alerts
|

M&A Open Innovation, and Its Obstacle: A Case Study on GCC Region

Abstract: Considering the effective growth in challenges and an urge in establishment for sustainable business, companies trading globally are inclined towards the implementation of highly efficient cross-border reallocations of revolving capital. The prominent objective of this research paper is therefore the clear identification of the active key attributes and specifications of all strategic measures for efficient sustainable cross-border mergers and acquisitions (M&As) of the Islamic companies in the Gulf region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…According to [119], the culture of the dynamics of open innovation is cyclical and follows a quadruple helix, composed of actors from industry, government, society, and university. The results presented in Table 8 show exactly open innovation variables that are directly related to one or more agents of the micro and macro dynamics of the quadruple helix.…”
Section: Seven Variables Related To Innovation Processes ([Market_needs] [Trends_tech] [Part_coop] [Innov_ideas] [Innov_pract] [Adapt_flementioning
confidence: 99%
“…According to [119], the culture of the dynamics of open innovation is cyclical and follows a quadruple helix, composed of actors from industry, government, society, and university. The results presented in Table 8 show exactly open innovation variables that are directly related to one or more agents of the micro and macro dynamics of the quadruple helix.…”
Section: Seven Variables Related To Innovation Processes ([Market_needs] [Trends_tech] [Part_coop] [Innov_ideas] [Innov_pract] [Adapt_flementioning
confidence: 99%
“…Cultural and religious norms have been found to be the primary factors in influencing consumer spending and, in turn, product development. Moreover, Bindabel (2020) investigated the importance of culture as a paradigm in fostering open innovation in the Gulf Cooperation Council countries. The results showed that the respondents generally agreed on how the Shariah compliance company decided on matters of innovation and M&A.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Thus, during this study of different types of innovation, the process of open innovation emerges and is adapted according to companies' needs [26]. Open innovation is cyclical and follows a quadruple helix, composed of actors from the industry, government, universities, and society [27]. A critical part of the open innovation process involves the knowledge management required to achieve higher levels of industrial performance through the correct use of technologies [8].…”
Section: Literature Review Of Open Innovationmentioning
confidence: 99%
“…Innovation is a cutting-edge goal for companies interested in expanding their businesses, involves different types of change and depends on an organization's resources, capabilities, strategies, and requirements [25]. As a result, customer attraction and company performance are influenced by innovative strategies and activities [27]. For [8], the dynamics of innovation are cyclical and follow a quadruple helix, composed of actors from the industry, government, and universities, and could be leveraged in innovation environments.…”
Section: Literature Review Of Open Innovationmentioning
confidence: 99%